Transumbilical Arterial Access for Embolization of a Hepatic Vascular Tumor in a Critically Ill Premature Neonate - Khoury, Joe; Yeisley, Christopher D. (Journal of Clinical Interventional Radiology ISVIR, 2024)
Catheter-based interventions are relatively rare in the neonate population but serve as an invaluable tool in managing many pathologies. Here we present a case report of a neonate with a vascular hepatic tumor managed by embolization via transumbilical access. In neonates, the small size of the common femoral artery makes cannulation difficult and is thought to increase the risk of catheter-associated thrombosis and ischemia. Often, these patients reside in the neonatal intensive care unit (NICU) and already have an umbilical artery catheter (UAC) in place, which can be used as an effective alternative route of vascular access to carry out life-saving interventions.
Keywords: transumbilical; embolization; neonate